Distributed pedagogical leadership functions in Early Childhood Education settings in Finland - Heikka, Johanna; Suhonen, Katja (Southeast Asia Early Childhood Journal, 2019)
The topic of distributed pedagogical leadership has attracted researchers’ interest in early childhood education leadership. A growing body of research focuses on investigating leadership enacted between directors and teachers in ECE settings. This small-scale study aimed at identifying the functions of distributed pedagogical leadership in ECE and understanding the interdependence of leadership enactments by the centre directors and ECE teachers within ECE settings. Data on the perceptions of six ECE professionals, two ECE centre directors, two ECE teachers and two child care nurses on distributed pedagogical leadership were collected via individual interviews and written documents. The results indicated that the studied ECE professionals perceived the core functions of distributed pedagogical leadership as constructing shared visions, goals and mutual values between centre staff, developing ECE pedagogy within the centre, facilitating learning and expertise of educators, building the operational structures and the culture of the centre and enhancing efficient and participative decision-making within centres. Within all the five functions of distributed pedagogical leadership, the leadership enactment included responsibilities at both the centre level enacted by the centre directors, and at the team level enacted by the ECE teachers. All the five functions were operated within ECE centres in a way in which they had separate but interdependent leadership responsibilities. The study clearly indicated that the teachers played an active role in leading pedagogical development in their teams, and teacher leadership worked as a mediator of pedagogical leadership within the whole centre.